2006
DOI: 10.1080/02844310600574072
|View full text |Cite
|
Sign up to set email alerts
|

Vascularised bone graft for the treatment of non-union of the scaphoid

Abstract: A 4/5 compartment pedicled vascularised bone graft from the distal radius combined with internal fixation with a Herbert type cannulated screw was used to treat non-union fractures of the proximal pole of the scaphoid in 13 patients. Non-union was identified on plain radiographs alone. Uneventful clinical and radiological healing was achieved in 11 patients. One patient had progressive signs of failure of the fixation of the screw at the proximal pole; the screw was changed and the fracture was stable at reope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Several methods of transferring a VBG to the scaphoid have been reported in the literature. 14,15 These include the pronator quadratus pedicled bone graft, pedicled grafts based on the ulnar artery or the palmar carpal artery, the radial styloid fasciosteal graft, and pedicled grafts from the index finger metacarpal and the thumb metacarpal. Free VBGs from the iliac crest and the medial femoral supracondylar region have also been reported.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Several methods of transferring a VBG to the scaphoid have been reported in the literature. 14,15 These include the pronator quadratus pedicled bone graft, pedicled grafts based on the ulnar artery or the palmar carpal artery, the radial styloid fasciosteal graft, and pedicled grafts from the index finger metacarpal and the thumb metacarpal. Free VBGs from the iliac crest and the medial femoral supracondylar region have also been reported.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Several methods of transferring a vascularized bone graft to the scaphoid have been reported in the literature. 35,36 These include the pronator quadratus pedicled bone graft, pedicled grafts based on the ulnar artery or the palmar carpal artery, the radial styloid fasciosteal graft, and pedicled grafts from the index finger metacarpal and the thumb metacarpal. Free vascularized bone grafts from the iliac crest and the medial femoral supracondylar region have also been reported.…”
Section: Scaphoid Nonunionsmentioning
confidence: 99%
“…35,36 This raises the important question of whether or not improvement of the vascularity of the proximal pole would increase rates of union in cases with AVN. Recently, a meta-analysis found that vascularized bone grafting achieved an 88% union rate compared with a 47% union rate with screw and intercalated wedge fixation in scaphoid nonunions with AVN.…”
Section: Scaphoid Nonunionsmentioning
confidence: 99%
“…1). One group contains all the VBFs that are retrieved from the dorsal radius, 9,[13][14][15] based on the 2,3 ICSRA (2,3-intercompartmental, supraretinacular art. ), the four ECA (fourth extensor compartment art.)…”
Section: Methodsmentioning
confidence: 99%